Immune activation following PD-L1 inhibitor plus chemoradiotherapy in locally advanced rectal cancer: a retrospective, single-arm study - Fan, Shaoqing; Zhao, Zeming; Meng, Qingyu; Wang, Haiqian; Yu, Bin; Niu, Wenbo (Frontiers in Immunology, 2025)
BackgroundLocally advanced rectal cancer (LARC) is challenging due to high recurrence rates and poor responses to neoadjuvant chemoradiotherapy (nCRT). Combining nCRT with immunotherapy may enhance antitumor immunity by modifying the tumor microenvironment (TME). This study evaluates the efficacy of nCRT with PD-L1 inhibitor envafolimab in LARC and explores its impact on TME.MethodsIn this retrospective, single-arm design study, 36 LARC patients (T3+/N1-2/M0) received long-course radiotherapy (50.4 Gy/28 fractions) with capecitabine, followed by two cycles of XELOX chemotherapy and envafolimab. Pathological complete response (pCR) and tumor regression grade (TRG) were assessed post-surgery. Immunohistochemical analysis quantified CD4+, CD8+ T cells, and CD56+ NK cell infiltration in paired pre- and post-treatment tumor tissues.ResultsThe pCR rate was 47.2% (17/36), with 94.4% and 86.1% achieving T- and N-downstaging. Post-treatment tumor-infiltrating lymphocytes (TILs) increased, with CD8+ T cells showing the most significant infiltration (Grade 3: +6 cases, P<0.05). Higher baseline TIL density correlated with better TRG outcomes (TRG0-2: 94.4% vs. TRG3: 5.6%).ConclusionnCRT combined with envafolimab enhances immune cell infiltration, particularly CD8+ T cells, achieving high pCR rates in LARC. This approach enhances cytotoxic immunity while addressing immunosuppressive barriers. Further studies should explore strategies to overcome TME resistance.